Side-channel attacks analisys against NTRU-similar algorithm - Kachko, O.G.; Gorbenko, Yu.I.; Akolzina, O.S. (Radiotekhnika, 2018)
The results of NTRU-similar algorithm analysis with respect to resistance against side-channel attacks are given. Proposals of defending these attacks are given. The evaluations of how many keys will be reduced with key space limitations of key data (which are needed to ensure the properties of random sequences) are made.